Karakteristik Wirausaha Mapan dan Potensial Ekspor (Studi Pada Wirausaha Mapan Di Kota Pekalongan) - Suwandi, Suwandi (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
The focus of this study is entrepreneurs established with the potential to export. The result is that the characteristics of established export potential entrepreneurs are characterized by the highest ability in terms of finding opportunities for markets for products produced, actively seeking information and being creative-innovative. But on the other hand moderate courage to bear the risk, and confidence. The export potential of an established Entrepreneur is high, due to the availability of overseas customers or buyers, and the familiarity of established entrepreneurs in utilizing technology to support the export business. Also sufficient potential is in terms of the depth of export activities that can be carried out, and the potential that can be exported.